2013
DOI: 10.1128/jvi.01807-13
|View full text |Cite
|
Sign up to set email alerts
|

Efficiency of E2-p7 Processing Modulates Production of Infectious Hepatitis C Virus

Abstract: Previous studies indicate that the processing of hepatitis C virus (HCV) E2-p7-NS2 precursor mediated by host signal peptidase is relatively inefficient, resulting in the accumulation of E2-p7-NS2 and E2-p7 precursors in addition to E2 in mammalian cells. In this study, we discovered that a significant inhibition of the processing at an E2-p7 junction site is detrimental for HCV production, whether it was caused by the mutations in p7 or by the strategic introduction of a mutation at a terminal residue of E2 t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

3
70
0

Year Published

2013
2013
2019
2019

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 18 publications
(73 citation statements)
references
References 50 publications
3
70
0
Order By: Relevance
“…The results of our recent study suggested that p7 regulates NS2 localization to punctate sites near lipid droplets (punctate LD [see arrows in Fig. 1C]), which are considered putative virus assembly sites (10,12,13,16,20), and modulate virus production (10). However, the biochemical characteristics of these virus assembly sites are currently unknown.…”
Section: Resultsmentioning
confidence: 99%
See 4 more Smart Citations
“…The results of our recent study suggested that p7 regulates NS2 localization to punctate sites near lipid droplets (punctate LD [see arrows in Fig. 1C]), which are considered putative virus assembly sites (10,12,13,16,20), and modulate virus production (10). However, the biochemical characteristics of these virus assembly sites are currently unknown.…”
Section: Resultsmentioning
confidence: 99%
“…Construction of HJ3-5 and its derivatives, including p7(KRAA), E2(AR), E2(AR)/IRES, HA p7, and HA p7/IRES, were described previously (8,10,16). To generate ⌬p7 mutants, the p7 sequence from HJ3-5/p7/IRES (10) was deleted by using the QuikChange II XL sitedirected mutagenesis kit (Stratagene, La Jolla, CA) with primer pairs encoding the C-terminal sequence of E2 and the N-terminal sequence of encephalomyocarditis virus (EMCV) internal ribosomal entry site (IRES): 5=-CATATCCCAAGCGGAGGCGTGAGTTTAAACAGACCAC AACGG-3= and 5=-CCGTTGTGGTCTGTTTAAACTCACGCCTCCGCT TGGGATATG-3=, respectively.…”
Section: Methodsmentioning
confidence: 99%
See 3 more Smart Citations